2005
DOI: 10.1103/physrevb.71.113203
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic temperature in magnetically doped amorphous semiconductors

Abstract: The introduction of magnetic moments such as Gd into amorphous Si produces dramatic effects in electrical transport below a characteristic temperature T * . Below T * , the conductivity of the magnetically doped systems is strongly suppressed compared to equivalent nonmagnetic Y doped samples, and displays enormous negative magnetoresistance. T * occurs at relatively high temperatures ͑ϳ10-100 K͒ and decreases sharply with increasing Gd concentration, passing smoothly through the metal-insulator transition. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…This increase is in stark contrast to the decreasing T* (and T') with increasing x seen in a-Gd x Si 1-x and a-Gd x Ge 1-x , as well as ternary a-Gd x Y y Si 1-x alloys for constant x, and increasing y, which was interpreted as a consequence of increased screening of electron-moment interactions with the increasing metallicity associated with increasing x. 21 The dependence on x seen in Fig. 11 suggests that screening plays little or no role in the T-dependence of MR for ta-C 1-x :Gd x and sputtered a-Gd x C 1-x , unlike in a-Gd x Si 1-x and a-Gd x Ge 1-x .…”
Section: Rkky-like (The Lack Of Crystallinity Makes the Theory Necessmentioning
confidence: 38%
See 1 more Smart Citation
“…This increase is in stark contrast to the decreasing T* (and T') with increasing x seen in a-Gd x Si 1-x and a-Gd x Ge 1-x , as well as ternary a-Gd x Y y Si 1-x alloys for constant x, and increasing y, which was interpreted as a consequence of increased screening of electron-moment interactions with the increasing metallicity associated with increasing x. 21 The dependence on x seen in Fig. 11 suggests that screening plays little or no role in the T-dependence of MR for ta-C 1-x :Gd x and sputtered a-Gd x C 1-x , unlike in a-Gd x Si 1-x and a-Gd x Ge 1-x .…”
Section: Rkky-like (The Lack Of Crystallinity Makes the Theory Necessmentioning
confidence: 38%
“…10 -3 , 1% or 10%) OR by comparing zero-field σ(T) to σ(T) for non-magnetically doped analogues a-Y x Si 1-x or a-Y x Ge 1-x . 6,21 The latter method is very effective for metallic samples (x>0.14 in a-Gd x Si 1-x and a-Gd x Ge 1-x ) because it is a zero field measurement and provides an unambiguous characteristic temperature which we defined as T*, but is ineffective for insulating samples, briefly because the temperature dependence is not a simple power law and the dependence on x is far too strong to allow simple comparison to nonmagnetic analogs. The former method, based on magnetoresistance, gives a temperature which we will here call T'; T' depends on the magnitude chosen for the cutoff MR, but since MR vanishes exponentially with increasing temperature in both a-Gd x Ge 1-x and a-Gd x Si 1-x , the choice is not significantly important.…”
Section: Rkky-like (The Lack Of Crystallinity Makes the Theory Necessmentioning
confidence: 99%
“…13,14 Previ-ous studies [13][14][15] showed that for 0.04Ͻ x Ͻ 0.19 such films are classical spin glasses with sharp cusps in susceptibility ͓at about T = 6.5 K for x = 0.19 ͑Ref. 13͔͒ driven by mixed ferromagnetic and antiferromagnetic Gd-Gd interactions mediated by conduction electrons.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The introduction of transition metal elements such as Nb, Mo, or Fe into amorphous semiconductors such as Si leads to increased conductivity and a metal-insulator transition ͑MIT͒ for metal concentrations around 10-15 at. 6 Amorphous Si alloys have been studied after thermal treatment and show the formation of nanometer-sized grains. 1 Introduction of the magnetic element Gd has similarly been shown to lead to a MIT for amorphous Gd-Si alloys ͑a-Gd x Si 1−x ͒ with x = 14.0 at.…”
Section: Introductionmentioning
confidence: 99%